Posterior Reversible Encephalopathy Syndrome (PRES): Pathophysiology and Neuro-Imaging - Anderson, Redmond-Craig; Patel, Vishal; Sheikh-Bahaei, Nasim; Liu, Chia Shang J.; Rajamohan, Anandh G.; Shiroishi, Mark S.; Kim, Paul E.; Go, John L.; Lerner, Alexander; Acharya, Jay (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) represents a unique clinical entity with non-specific clinical symptoms and unique neuroradiological findings. This syndrome may present with a broad range of clinical symptoms from headache and visual disturbances to seizure and altered mentation. Typical imaging findings include posterior-circulation predominant vasogenic edema. Although there are many well-documented diseases associated with PRES, the exact pathophysiologic mechanism has yet to be fully elucidated. Generally accepted theories revolve around disruption of the blood-brain barrier secondary to elevated intracranial pressures or endothelial injury. In this article, we will review the clinical, typical, and atypical radiological features of PRES, as well as the most common theories behind the pathophysiology of PRES. Additionally, we will discuss some of the treatment strategies for PRES related to the underlying disease state.